Orbital Surgical Guidelines—Clinical Evaluation - Krauss, Howard R. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Orbital disorders may present with change in form or function or may be discovered incidentally during clinical or imaging evaluations. A standardized orbital clinical examination, with appropriate ancillary tests, is helpful in narrowing the differential diagnosis and in the development of plans for management, with an eye toward minimizing the morbidity of the disease or its treatment. Evaluation and management may best be performed with a multidisciplinary team, which has become more common in skull base surgery.
Keywords: orbit; skull base; neuro-ophthalmologist; optical coherence tomography; orbital echography; orbital; surgery